Quantitative attribution of seasonal runoff variations in the Yellow River Basin under unsteady conditions using a modified Budyko framework - Junjie Wang; Yuning Chi; Shaoxiong Zhang; Bing Shi; Liting Zhang; Chenjun Du; Xin Li; Baoqi Li; Liqin Yang; Lei Huang; Dian Yuan; Kaiyang Qiu; et al. (Journal of Hydrology, 2026)

Divergent hydrological responses of multi-depth soil moisture variability to multiple factors on the Loess Plateau, China - Junjie Wang; Shaoxiong Zhang; Yuning Chi; Bing Shi; Xin Li; Baoqi Li; Panxing He (Journal of Hydrology, 2026)

Outstanding extrinsic reversible self-healing material for commercial epoxy coating: Dynamic chemistry-based supramolecular interpenetrating polymer networks - Panhua Li; Tingting Luo; Xuanyu Lv; Yuning Shi; Bosen Zhang; Kaixuan Ma; Wanchun Guo; Kesong Tian; Xueai Li; Hui Ying Yang; Haiyan Wang (Chemical Engineering Journal, 2026)

Structural control of nitrogen-doped carbon nanotubes embedded with magnetic nanoparticles enabling tunable electromagnetic response and multifunctional flexible film - Jiantao Sun; Kexin Jin; Jing Wang; Xueai Li; Yue Li; Yuning Shi; Chunsheng Wang; Wanchun Guo; Kesong Tian; Haiyan Wang; Yingdan Liu (Chemical Engineering Journal, 2026)

Highly homogeneous dispersed Ni/Co nanoparticles in carbon controlled by ion coordination to trigger polarization for enhanced microwave absorption - Yuning Shi; Shuang Zhang; Xueai Li; Chunsheng Wang; Hang Li; Jinjin Yang; Kexin Jin; Wanchun Guo; Kesong Tian; Yahui Wang; Haiyan Wang (Chemical Engineering Journal, 2026)

Physiological, metabolic, and transcriptional responses of contrasting sorghum (Sorghum bicolor (L.) Moench) cultivars to drought - Chunlei Zou; Junming Ma; Tao Jin; Xinyu Wang; Xiaoxia Shi; Yuning Hao; Zihao Guo; Xiaolong Wei; Chunlai Zhang; Zhijia Gai (Plant Cell Reports, 2026)

Comparative experimental study and optimization of frost heave inhibiting modifiers for clayey silt - Yi Cao; Yansen Wang; Zhijie Guo; Meng Ren; Yuning Wang; Yingxia Hou; Rongjian Shi; Jianzhou Wang (Cold Regions Science and Technology, 2025)

Bifunctional electrolyte inducing uniform Zn deposition and suppressing polyiodide shuttle for long life zinc-iodine batteries with low-temperature applicability - Xiaorong Shi; Lei Dai; Jianjian Zhang; Chang Sun; Zhu Long; Yuning Li (Chemical Engineering Journal, 2025)

Reducing dye pollution: Sustainable reuse of colored cotton waste powders in washing-free flat screen printing - Chengyong Gao; Yuning Liu; Tieling Xing; Xiao Li; Sheng Shi (Sustainable Chemistry and Pharmacy, 2025)

Initiative invasion promoted photoelectrocatalytic antibacterial function on ZIF-67@CoO@Co foil photoanode - Mengna Ding; Qin Zhang; Fengyan Shi; Liping Zhou; Xinchun Guo; Qiuyue Li; Liulin Luo; Yingchun Miao; Yuning Huo (Chemical Engineering Journal, 2025)

Salinity-dependent effects of seawater acidification on growth, photosynthetic physiology and biochemistry of the invasive macroalga Codium fragile - Yaoyao Chu; Yunyun Shi; Yuning Xue; Lianghua He; Xiaodong Li; Xiangzhu Shi; Yinggu Kuang; Xinhua Chen; Chao Zhao (Algal Research, 2025)

Optimizing a link-based travel incentive scheme integrating personal carbon trading for low-carbon commuting - Bing Liu; Xiaolei Ma; Yuning Shi; Xiaohai Liu; Kun Gao; Qiong Tian; Wenwei Wang (Journal of Environmental Management, 2025)

The Cycles agroecosystem model: Fundamentals, testing, and applications - Armen R. Kemanian; Yuning Shi; Charles M. White; Felipe Montes; Claudio O. Stöckle; David R. Huggins; Maria Laura Cangiano; Giovani Stefani-Faé; Rachel K. Nydegger Rozum (Computers and Electronics in Agriculture, 2024)

Magnetic bimetallic nanoparticles confined growth for enhancement of electromagnetic loss in void@Fe@SiO2/Co/C particles - Xueai Li; Kexin Jin; Xiangyan Qu; Yuning Shi; Chunsheng Wang; Wanchun Guo; Kesong Tian; Yahui Wang; Haiyan Wang (Chemical Engineering Journal, 2024)

DNN–GA–RF prediction model for rock strength indicators based on sound level and drilling parameters - Zhenghao Liu; Weida Wang; Yuning Chen; Shaoshuai Shi; Junjie Wang; Ruijie Zhao (Bulletin of Engineering Geology and the Environment, 2024)

Regulation of tumorigenesis and ferroptosis in non-small cell lung cancer by a novel BBOX1-AS1/miR-326/PROM2 axis - Jinlu An; Jiang Shi; Chao Yang; Junfang Luo; Yuning Li; Jie Ren; Yuanjun Lv; Yang Zhang (Molecular and Cellular Biochemistry, 2024)

Improving Water Quality in a Sea Bay by Connecting Rivers on Both Sides of a Harbor - Yuning Chi; Wenming Zhang; Yanling Liu; Xiaoyu Zhang; Wanqing Chi; Bing Shi (Journal of Marine Science and Engineering, 2024)
Improving water quality is imperative for many sea bays, including Laizhou Bay, China, to achieve sustainable marine development. In 2010, two 17.3 km long sand-retaining embankments were built in southwestern Laizhou Bay, which weakened the nearshore hydrodynamics and seriously impacted the water quality. To mitigate this issue, this study proposes connecting the two rivers on both sides of the embankments to improve the hydrodynamics and thus water exchange in the sea bay. The effectiveness was examined with a numerical model using Mike 21, which was validated for both tidal current velocity and direction at six monitoring locations in the sea bay. The results show that over 53% of the core research area displays an increase (0.0–0.4 m/s) in tidal current speed after the connection, primarily in and around the Haihengwei Fishing Port. Meanwhile, the Eulerian residual currents in the Haihengwei Fishing Port, Mi River estuary and Bailang River estuary become substantially larger (with a maximum increase of 0.16 m/s). In addition, the net transport distance of particles released near the connection increases by up to 39.89 km in one month. Overall, this case study demonstrates that connecting rivers next to a harbor can effectively improve hydrodynamics and thus improve water quality in the bay.

Application and development of zero-valent iron (ZVI)-based materials for environmental remediation: A scientometric and visualization analysis - Qiuju Wu; Yijie Sun; Zijing Luo; Xinyan Li; Yi Wen; Yuning Shi; Xuejia Wu; Xinni Huang; Yiyan Zhu; Chao Huang (Environmental Research, 2024)

Electronic structure modulation coupling with interface effect for great improving water electrolysis by multiple dimensional S doped MnCo2O4 nanorods/N doped C nanosheets hybrids - Liucheng Xia; Jinping Wang; Lili Bo; Wenping Shi; Yuning Zhang; Yuxing Shen; Xiaochao Ji; Xiaolin Guan; Yunxia Wang; Jinhui Tong (Chemical Engineering Journal, 2023)

Topography Mediates the Response of Soil CO2 Efflux to Precipitation Over Days, Seasons, and Years - Marissa Kopp; Jason Kaye; Yuting He Smeglin; Thomas Adams; Edward J. Primka; Brosi Bradley; Yuning Shi; David Eissenstat (Ecosystems, 2023)

Tradeoffs when interseeding cover crops into corn across the Chesapeake Bay watershed - Curt A. McConnell; Rachel K.N. Rozum; Yuning Shi; Armen R. Kemanian (Agricultural Systems, 2023)

Study on Complex Wake Characteristics of Yawed Wind Turbine Using Actuator Line Method - Tengyuan Wang; Shuni Zhou; Chang Cai; Xinbao Wang; Zekun Wang; Yuning Zhang; Kezhong Shi; Xiaohui Zhong; Qingan Li (Journal of Marine Science and Engineering, 2023)
In modern large-scale wind farms, power loss caused by the wake effect is more than 30%, and active yaw control can greatly reduce the influence of the wake effect by deflecting the wind turbine’s wake. The yawed wind turbine’s wake characteristics are complex, and a deep comprehension of a yawed turbine’s wake is necessary. The actuator line method combined with URANS (unsteady Reynold-averaged Navier–Stokes equations) is used to study the yawed wind turbine’s wake characteristics in this paper. Compared with an un-yawed wind turbine, a yawed one has two main characteristics, deflection and deformation. With an increasing yaw angle, turbine wake shows an increasing deflection. The results indicated that deflection at different height was different, the wake profile showed the biggest deflection at about the hub height, while the smallest deflection existed at the top and bottom of the yawed turbine’s wake. This can be visually demonstrated by the evolution of a kidney-shape velocity distribution at the vertical cross-section. Two-dimensional and three-dimensional presentations of velocity deficit distributions are presented in this paper. The evolution of an irregular kidney-shape distribution is discussed in this paper. It is formed by the momentum exchange caused by the counter-rotating vortex pair. The results indicated that the counter-rotating vortex pair was composed of the streamwise vortex flux brought by the tip vortex. Furthermore, when the wind turbine rotated clockwise and yawed clockwise, the negative vorticity of counter-rotating vortex first appeared in the upper left position.

Enhancement of thioethers removal by pre-oxidation-coagulation: Effects of background organic matter - Mengze Geng; Xin Huang; Baoyou Shi; Jianwei Yu; Chunmiao Wang; Yuning Du; Yili Wang (Science of The Total Environment, 2023)

Defect and interface engineering of templated synthesis of hollow porous Co3O4/CoMoO4 with highly enhanced electrocatalytic activity for oxygen evolution reaction - Liucheng Xia; Lili Bo; Wenping Shi; Yuning Zhang; Yuxing Shen; Xiaochao Ji; Xiaolin Guan; Yunxia Wang; Jinhui Tong (Chemical Engineering Journal, 2023)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)